Effectiveness Of Social Media Marketing Strategy and Visual Brand Identity on Instagram in Improving Brand Awareness Of Miricare Oil Business - Saragih, Ariahmand; Fikri, Miftah El (Economic: Journal Economic and Business, 2025)
This study aims to analyze the effectiveness of implementing social media marketing strategies and visual brand identity in increasing brand awareness of the Miricare Oil business. This strategy is applied to Instagram, which is a digital media that has developed into one of the social media platforms that can build relationships with customers and promote brands. The research method used is the mix methods method with a quantitative and qualitative approach, where data is obtained through distributing questionnaires to followers of the Instagram account @miricare.oil and observing the uploaded content. The implementation of social media marketing strategies and visual brand identity was carried out from February 11 to April 5, 2025 on the Instagram account @miricare.oil_official. The results of the study show that relevant, interactive, and consistent social media marketing strategies with the right target audience can increase user engagement. This study found that both elements simultaneously contributed significantly to increasing brand awareness of Miricare Oil. The combination of the two strategies using Instagram strategically with a cohesive visual approach can be an effective tool for building brand awareness in the digital technology era.